2017
DOI: 10.2516/ogst/2017017
|View full text |Cite
|
Sign up to set email alerts
|

CFD-PBM Coupled Simulation of an Airlift Reactor with Non-Newtonian Fluid

Abstract: -Hydrodynamics of an AirLift Reactor (ALR) with tap water and non-Newtonian fluid was studied experimentally and by numerical simulations. The Population Balance Model (PBM) with multiple breakup and coalescence mechanisms was used to describe bubble size characteristics in the ALR. The interphase forces for closing the two-fluid model were formulated by considering the effect of Bubble Size Distribution (BSD). The BSD in the ALR obtained from the coupled Computational Fluid Dynamics (CFD)-PBM model was valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…[ 23 ] Moreover, the characteristic bimodal BSD observed at higher Ug due to the presence of a larger range of bubbles is evident at 0.15 and 0.20 ms −1 . A similar observation was also confirmed by Han et al [ 25 ] using CMC.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…[ 23 ] Moreover, the characteristic bimodal BSD observed at higher Ug due to the presence of a larger range of bubbles is evident at 0.15 and 0.20 ms −1 . A similar observation was also confirmed by Han et al [ 25 ] using CMC.…”
Section: Resultssupporting
confidence: 88%
“…The higher rise velocity of larger bubbles reduced the gas residence time, thereby reducing gas holdup. The CFD study by Han et al [ 25 ] showed a bimodal BSD in aqueous CMC with an increase in Ug. The BSD changes from uniform, narrow, and monomodal to bimodal having large bubbles in the heterogeneous regime.…”
Section: Introductionmentioning
confidence: 99%
“…Other relevant studies where a CFD approach has been used to evaluate the hydrodynamics of internal-loop airlift reactors with Newtonian fluids are those carried out by Mohajerani et al (2012) and Nalband and Jalilnejad (2019). However, although non-Newtonian rheology can have a significant effect on the hydrodynamic performance of airlift reactors, to the best of our knowledge, the number of previous numerical studies dealing with these systems with non-Newtonian shear-thinning fluids has been scarcely addressed (Xu et al, 2015;Han et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As reported by a variety of studies, liquid-liquid dispersion has applications in a number of fields, ranging from the accurate measurement of drop size [4]to the study of mass transfers between phases [5,6]. Rheology issues were widely discussed throughout the conference [7], as was the development of new interfacial rheologytechniques [8]. Finally, multiphase flow modeling is obviously another major issue for the development of innovative techniques [7,9].…”
mentioning
confidence: 99%
“…Rheology issues were widely discussed throughout the conference [7], as was the development of new interfacial rheologytechniques [8]. Finally, multiphase flow modeling is obviously another major issue for the development of innovative techniques [7,9].…”
mentioning
confidence: 99%